1999
DOI: 10.1159/000006947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age, Heart Rate and Tricuspid Regurgitation on the Doppler Echocardiographic Evaluation of Right Ventricular Diastolic Function

Abstract: Pulsed-wave Doppler analysis of tricuspid inflow and hepatic venous flow allows the determination of multiple parameters of right-ventricular (RV) diastolic function. This study sought to evaluate the influence of heart rate, age and tricuspid regurgitation on Doppler parameters of RV diastolic performance. We studied 80 subjects (20 normal and 60 with RV pathology) with Doppler recordings of the tricuspid inflow and hepatic vein. All tricuspid Doppler parameters were dependent on heart rate, age or regurgitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Our observation of a redistribution of right atrial emptying with a greater dependence on booster pump function in healthy subjects C60 years is consistent with other studies that have shown a larger contribution of atrial contraction to right ventricular filling with age using conventional Doppler of transtricuspid and hepatic vein flow [11][12][13][14]. Our findings are also consistent with recent tissue Doppler imaging studies [3,13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our observation of a redistribution of right atrial emptying with a greater dependence on booster pump function in healthy subjects C60 years is consistent with other studies that have shown a larger contribution of atrial contraction to right ventricular filling with age using conventional Doppler of transtricuspid and hepatic vein flow [11][12][13][14]. Our findings are also consistent with recent tissue Doppler imaging studies [3,13].…”
Section: Discussionsupporting
confidence: 92%
“…This increases late left ventricular filling and pressure and maintains cardiac output [4]. Since there is also a decline in right ventricular diastolic function with age [11][12][13][14] and pulmonary arterial hypertension [16], it is tempting to speculate that similar mechanisms occur in the right sided cardiac chambers [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously Radetti et al (8) reported comparable findings in TS during GH treatment. Diastolic filling is known to be heart rate dependent (25,26), and correction for heart rate (which was significantly higher in our patients) resulted in comparable biventricular diastolic filling pattern between our patients and controls. As Radetti et al previously suggested, the changes seen in LV diastolic filling in TS probably should be regarded as an adaptation to the higher heart rates seen in TS, rather than an early representation of LV dysfunction (8).…”
Section: Cardiac Functionsupporting
confidence: 56%
“…Multiple Doppler‐derived echocardiographic parameters have been suggested to assess RV diastolic function: tricuspid E/A ratio, 4,5 early diastolic tricuspid annular velocity (Em), 6–8 RV annulus Em/Am, 8,9 E/Em, 10 RV MPI and IVRT, 8,11 and negative dP/dT 12 . However, most of these parameters have been limited by their sensitivity to respiratory alterations in preload and afterload, age, tricuspid regurgitation and heart rate 13–15 …”
mentioning
confidence: 99%